Problem of Selection and Properties of Lubricants for Ethelene High-Pressure Compressors. 5. Сompatibility of Oils with Polyethylene - Sirenko, H. O.; Martynyuk, M. I.; Svidersky, V. P.; Sulyma, I. V.; Ilnіtskyy R. V.; Shmaltser, N. V.; Kretov, M. I.; Zavoyko, A. M.; Kuzyshyn, O. V. (Physics and Chemistry of Solid State, 2017)
The technology of obtaining and properties of ethylene compositions with different content of oils inside is researched. It is shown viscous-mechanical properties of polyethylene during the addition of a different quantity of lubricants. The results of researches of physics-mechanics and dielectric properties of polyethylene, synthesized during ingress of naphthene, with addition of 0,15% of different oils and thermooxidants.